CFD of a screw blade for standalone micro hydro generator - Suga Ganeshan, Kalaichalban (2013)
Archimedean screw is one of the oldest hydraulic machines. Previously, this screw runner is used to lift water from lower part to upper part. In this modern era, Archimedean screw is used to generate electricity using the reverse concept of the old Archimedean screw. The efficiency of the screw blade is depend on the parameters of the screw blade. The main aim in this paper is to determine the efficiency of the Archimedean screw at different inclination angle and angle of attack of the blades. Re-inversed concept of the old Archimedean screw was used and using k-epsilon turbulence method was applied to study the fluid flow behavior. Comparison between theoretical design and CFD was done to obtain the most effective inclination angle and angle of attack between blades. Results show the inclination angle 23.58º and angle of attack 75º was the most reasonable design. In future can be more determine on the orientation angle for future research in Archimedean screw.